Aetiology of uveitis in Sierra Leone, west Africa. - Ronday, M J (1996)
BACKGROUND: In 1992, non-onchocercal uveitis caused 9% of blindness, 8% of visual impairment, and 11% of uniocular blindness among patients visiting an eye hospital in Sierra Leone, west Africa. The aim of this study was to determine the aetiology of uveitis in this population. METHODS: General and ophthalmic examination complemented by serum and aqueous humour analyses for various infectious agents was performed for 93 uveitis patients and compared with serum (n = 100) and aqueous humour (n = 9) analysis of endemic controls. RESULTS: At the initial examination, 45 patients (48%) proved to be severely visually handicapped. After clinical and laboratory analyses, an aetiological diagnosis was established for 49 patients (52%). Toxoplasma gondii was the most important cause of uveitis (40/93; 43%). Anti-toxoplasma IgM antibodies were detected in serum samples of seven of 93 patients (8%) compared with one of 100 controls (1%, p < 0.05). At least six patients (15%) with ocular toxoplasmosis had acquired the disease postnatally. Antibodies against Treponema pallidum were detected in 18 of 92 patients (20%) and in 21 controls (21%). Other causes of uveitis were varicella zoster virus (one patient), herpes simplex virus (two patients), and HLA-B27 positive acute anterior uveitis with ankylosing spondylitis (one patient), while one patient had presumed HTLV-I uveitis. CONCLUSIONS: In a hospital population in Sierra Leone, west Africa, uveitis was associated with severe visual handicap and infectious diseases. Toxoplasmosis proved to be the most important cause of the uveitis. Although the distribution of congenital versus acquired toxoplasmosis in this population could not be determined, the results indicate an important role of postnatally acquired disease. The results further suggested minor roles for HIV, tuberculosis, toxocariasis, and sarcoidosis as causes of uveitis in this population.